Investigation of band gap and permittivity of the perovskite CaTiO3 in ultrathin layers. (24th September 2015) - Krause, A; Weber, W M; Pohl, D; Rellinghaus, B; Kersch, A; Mikolajick, T
Abstract: Simulations and experimental results of ultrathin layers of the model perovskite CaTiO3 prove its suitability for integration as a novel dielectric in industrial applications due to an excellent compromise between band gap and permittivity. The computational approach relies on density functional theory in the local density approximation for CaTiO3 and comparable perovskites. With low-energy EELS measurements, the band gap of 3.8–4.38 eV for CaTiO3 was determined with exceptional precision, using a monochromatic electron beam (80 kV acceleration voltage, 0.18 eV FWHM) in a high resolution scanning transmission electron microscopy setup. Results of capacitance voltage measurements of ultrathin CaTiO3 capacitors show an excellent permittivity of 102.3 for 17.8 nm layer thickness. DUV–VIS ellipsometric measurements are carried out to complete the picture of band gap and permittivity of CaTiO3 as a competing perovskite to SrTiO3 or others for possible integration in ultrathin capacitor stacks.